Implementasi Program Sosialisasi Peraturan Pemerintah Nomor 53 Tahun 2010 Tentang Disiplin Pegawai Negeri Sipil di Kabupaten Cirebon - Septiani, Nurlia; Suryaningsih, Margaretha; Marom, Aufarul (Journal of Public Policy and Management Review, 2014)
This research aims to analyze the implementation socialization program of Government Regulation Number 53 of 2010 concerning Civil Servants in Disciplinary of Cirebon Regency and the factors that influence of socialization program. Locus of this research is Badan Kepegawaian, Pendidikan dan Pelatihan Daerah Cirebon Regency in Bidang Pembinaan dan Kesejahteraan Pegawai as implementers of socialization program. This research used qualitative research methods explorative. Subjects in this research consisted from implementers and receives of socialization program. Â Results of research show that the implementation socialization program of Government Regulation Number 53 of 2010 concerning Civil Servants in Disciplinary of Cirebon Regency has reached with good results. Implementation of socialization program has some problem, that is the absence of Standard Operating Procedures for socialization program, uncoordinate placement and selection of employees make some problems in work time employees. Suggest for problems that influence implementation of socialization program that is make an analyze of Standard Operating Procedures as a reference implementation of socialization program and make fixed schedule for employees who give a socialization services.